REGULATION OF DRUGS PRODUCTION IN RUSSIA XVI AND XVII CENTURIES: VINEYARD, PHARMACOPOEIAS, LECHEBNIK - Y. I. Zelikson (Разработка и регистрация лекарственных средств, 2019)
The article provides an overview of the first medical manuscript sources that regulate drugs production in Russia XVI and XVII centuries: vineyard, lechebnik, pharmacopoeias. Here are the details about the first pharmacies - Here are the details about the first pharmacies - green benches, an Pharmaceutical decree, which functions include control the drug production.